REALISTICALLY IMAGINING THE INTERNET: OVERCOMING (MIS)PERCEPTIONS WHEN EDUCATING POLICYMAKERS AND THE PUBLIC - Forno, Richard (AoIR Selected Papers of Internet Research, 2015)
This paper will explore the correlations between popular Internet imaginings and global technology policy events by asking how these cognitive disconnects can be overcome to foster better understanding of the Internet by global society. and especially by its elected officials. Can we prevent another oversimplified "the Internet is a series of tubes" moment to ensure that knowledge about the Internet, cyberspace, and its related technologies used in crafting Internet policy remains based on fact and reality instead of stereotypes, fantasy, or wishful thinking?